2022
DOI: 10.1002/pat.5780
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and selection using FAHP‐TOPSIS technique of zirconia, titanium oxide, and marble dust powder filled dental restorative composite materials

Abstract: The article aimed to develop and characterize the nano-micro ceramic particle-filled polymer-based composite as dental materials. The current study also deals with the ranking of dental composites using a hybrid fuzzy analytic hierarchy process (FAHP)fuzzy technique for order of preference by similarity to ideal solution (FTOPSIS) methodology. Dental composites were fabricated from resin matrix and ceramic particulates. Two different series were fabricated. Zirconia, titanium oxide, and marble dust powder were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is difficult to explain which dental formulation is more crucial than others. But it can be solved after determining the weight criteria of different material performances and evaluating the ranking of the alternative dental composite [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain which dental formulation is more crucial than others. But it can be solved after determining the weight criteria of different material performances and evaluating the ranking of the alternative dental composite [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that nanoparticles [31,32], polymers [33][34][35][36], and nanocomposites [37] could be used for water treatment. TOPSIS has been used for the selection of polymers [38][39][40][41], nanomaterials [42][43][44], and machine process parameters [45]. It has been shown to be efficient for optimizing analytic procedures and normalization methods [46,47], and materials [48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…During recent years, TOPSIS has been used for the optimization and analysis of polymers [50][51][52][53], nanomaterials [54][55][56], and machine process or operation parameters [57][58][59][60]. More investigations would be required to develop this algorithm for the manufacturing optimization of materials and their preparation procedures for environmental studies.…”
Section: Discussionmentioning
confidence: 99%